Interactive storytelling : 12th International Conference on Interactive Digital Storytelling, ICIDS 2019, Little Cottonwood Canyon, UT, USA, November 19-22, 2019, Proceedings /: 12th International Conference on Interactive Digital Storytelling, ICIDS 2019, Little Cottonwood Canyon, UT, USA, November 19-22, 2019, Proceedings. (2019) - Unknown
No abstract available